LED technology in public light system of the Municipality of Rome: an economic and financial analisys - Campisi, Domenico; Gitto, Simone; Morea, Donato (International Journal of Energy Economics and Policy, 2017)
This study evaluates an investment project concerning the redevelopment of the public lighting of the Municipality of Rome. In particular, we consider the replacing of the traditional lamps of the system with LED lamps. We consider the factors that affect this kind of project: the cost of energy, the manteinance cost, the investment cost and the Weighted Average Cost of Capital (WACC). Our results underline the reduction of energy consumption and of the maintenance costs, lower emissions of CO2 into the atmosphere, the reduction of light pollution, the positive effects on road safety and the indipendence by incentives. Keywords: LED technology, CO2 emissions, public lighting JEL Classification: H54